2005
DOI: 10.1093/ajcn/81.4.864
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of home-based therapy with ready-to-use therapeutic food with standard therapy in the treatment of malnourished Malawian children: a controlled, clinical effectiveness trial

Abstract: Home-based therapy with RUTF is associated with better outcomes for childhood malnutrition than is standard therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
267
4
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(285 citation statements)
references
References 12 publications
11
267
4
3
Order By: Relevance
“…Three trials compared home based management of RUTF with the standard practise using F-100 formula at therapeutic centres. Of these, two studies started home therapy after initial stabilization at a facility (6)(7)(8). A previously conducted meta-analysis showed an advantage of weight gain of 3.0 g/kg/day (WMD = 3.0; 95% CI= -1.70, 7.70) in favour of RUTF against F-100; however, the results were statistically not significant (4).…”
Section: Controlled Trialsmentioning
confidence: 99%
“…Three trials compared home based management of RUTF with the standard practise using F-100 formula at therapeutic centres. Of these, two studies started home therapy after initial stabilization at a facility (6)(7)(8). A previously conducted meta-analysis showed an advantage of weight gain of 3.0 g/kg/day (WMD = 3.0; 95% CI= -1.70, 7.70) in favour of RUTF against F-100; however, the results were statistically not significant (4).…”
Section: Controlled Trialsmentioning
confidence: 99%
“…Strategies that rely on ready-to-use-therapeutic-foods (RUTFs) have proven effective in the treatment of moderate and severe acute malnutrition (Ciliberto et al, 2005;Dossou, Ndour, Briend & Wade, 2003;Manary, Ndekha, Ashorn, Maleta, & Briend, 2004;Matilsky, Maleta, Castleman, & Manary, 2009;Sandige, Ndekha, Briend, Ashorn, & Manary, 2004). Similarly, distributions of Ready-to-Use-Supplementary-Food (RUSF) have been shown to reduce moderate and severe acute malnutrition (Adu-Afarwuah et al, 2007;Defourny et al, 2009;Kuusipalo, Maleta, Briend, Manary, & Ashhorn, 2006;Patel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence and operational experience have demonstrated that community-based treatment of uncomplicated SAM is effective (4)(5)(6)(7) and cost-effective (8,9) .…”
mentioning
confidence: 99%